Efficacy and tolerability of an undenatured type II collagen supplement in modulating knee osteoarthritis symptoms: a multicenter randomized, double-blind, placebo-controlled study - Lugo, James P.; Saiyed, Zainulabedin M.; Lane, Nancy E. (Nutrition journal, 2016)
Undenatured type II collagen (UC-II) is a nutritional supplement derived from chicken sternum cartilage. The purpose of this study was to evaluate the efficacy and tolerability of UC-II for knee osteoarthritis (OA) pain and associated symptoms compared to placebo and to glucosamine hydrochloride plus chondroitin sulfate (GC). One hundred ninety one volunteers were randomized into three groups receiving a daily dose of UC-II (40 mg), GC (1500 mg G & 1200 mg C), or placebo for a 180-day period. The primary endpoint was the change in total Western Ontario McMaster Universities Osteoarthritis Index (WOMAC) from baseline through day 180 for the UC-II group versus placebo and GC. Secondary endpoints included the Lequesne Functional Index (LFI), the Visual Analog Scale (VAS) for pain and the WOMAC subscales. Modified intent-to-treat analysis were performed for all endpoints using analysis of covariance and mixed model repeated measures, while incremental area under the curve was calculated by the intent-to-treat method. At day 180, the UC-II group demonstrated a significant reduction in overall WOMAC score compared to placebo (p = 0.002) and GC (p = 0.04). Supplementation with UC-II also resulted in significant changes for all three WOMAC subscales: pain (p = 0.0003 vs. placebo; p = 0.016 vs. GC); stiffness (p = 0.004 vs. placebo; p = 0.044 vs. GC); physical function (p = 0.007 vs. placebo). Safety outcomes did not differ among the groups. UC-II improved knee joint symptoms in knee OA subjects and was well-tolerated. Additional studies that elucidate the mechanism for this supplement's actions are warranted. CTRI/2013/05/003663 ; CTRI/2013/02/003348 .